1997
DOI: 10.1073/pnas.94.3.1029
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of a soybean β-glucan-elicitor-binding protein

Abstract: ABSTRACT␤-Glucan elicitor (GE), released from the cell wall of the phytopathogenic fungus Phytophthora megasperma by soybean glucanases, causes defense reactions in soybean. A GE-binding protein (GEBP) was purified from the membrane fraction of soybean root cells, and its cDNA was isolated. Expression of the cDNA clone in tobacco suspension cultured cells and in Escherichia coli conferred GE-binding activity to both. An antibody against the recombinant protein was found to inhibit the GE binding with the soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
118
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(120 citation statements)
references
References 42 publications
0
118
0
2
Order By: Relevance
“…For two of these elicitors, AvrPto (25) and syringolide (26), soluble, cytoplasmic proteins acting as receptors have been identified. Up to date, the only membrane-associated receptor for which successful biochemical purification and cloning has been described is the binding site for the fungal glucan elicitor (27,28). Interestingly, the functional form of the binding protein appeared to be associated with the plasma membrane, but much of the protein, as demonstrated immunologically, appeared to reside in the soluble fraction in an apparently nonfunctional form (28).…”
Section: The High Affinity Binding Site In a Thaliana Exhibits Charamentioning
confidence: 99%
“…For two of these elicitors, AvrPto (25) and syringolide (26), soluble, cytoplasmic proteins acting as receptors have been identified. Up to date, the only membrane-associated receptor for which successful biochemical purification and cloning has been described is the binding site for the fungal glucan elicitor (27,28). Interestingly, the functional form of the binding protein appeared to be associated with the plasma membrane, but much of the protein, as demonstrated immunologically, appeared to reside in the soluble fraction in an apparently nonfunctional form (28).…”
Section: The High Affinity Binding Site In a Thaliana Exhibits Charamentioning
confidence: 99%
“…Immunolocalization studies revealed a Ca 2 ϩ -dependent association of Pseudomonas syringae pv syringae harpin with tobacco cell walls (Hoyos et al, 1996), but harpin-induced K ϩ /H ϩ exchange at the plant plasma membrane and subsequent plasma membrane depolarization (Hoyos et al, 1996;Pike et al, 1998) raised questions regarding the concept of a cell wall binding site mediating such responses. Alternatively, bacterial elicitors may be recognized by the plant just like elicitors derived from phytopathogenic fungi and oomycetes, which bind to plasma membrane proteins (Nürnberger et al, 1995;Mithöfer et al, 1996;Umemoto et al, 1997;Bourque et al, 1999). An example of this phenomenon is provided by the recent identification of a 115-kD tomato microsomal membrane protein that binds the bacterial flagellin-derived elicitor flg22 (Meindl et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This type of resistance requires that plants are able to recognize a broad spectrum of microbes, and the currently accepted view is that plants have evolved pathogenassociated molecular pattern (PAMP)-triggered immunity to recognize features that are common to many microbes via cell surface receptors (Thordal-Christensen, 2003;Nü rnberger et al, 2004). Several PAMPs have been identified from plant pathogens, including flagellin and elongation factor Tu from Gramnegative bacteria (Felix et al, 1999;Kunze et al, 2004) as well as chitin and b-glucan from fungi and oomycetes (Umemoto et al, 1997;Kaku et al, 2006). Although PAMPs may trigger immune responses in susceptible plants, it is considered that adapted pathogens have evolved to overcome or evade basal resistance so that these responses are no longer sufficient to completely restrict pathogen infection (Jones and Dangl, 2006;de Wit, 2007).…”
Section: Introductionmentioning
confidence: 99%